Penguatan Kompetensi Professional Guru PAI Dalam Menghadapi Era Society 5.0 (Studi Deskriptif Strategi Peningkatan Mutu Guru PAI di SMP Negeri 16 Samarinda) - Muhammad Nasikin; Umar Fauzan; Noor Malihah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2023)
The era of Society 5.0 brought extraordinary changes in all human life in various fields, including health, economy, technology and education. In the field of education, the existence of teachers is very important in order to shape the character building of students to control the negative effects of technology and make good use of technology. The purpose of this study is to find out how the challenges of PAI teachers are in the era of society 5.0', how is the strategy for strengthening the professional competence of PAI teachers at SMP Negeri 16 Samarinda in accordance with the demands of the era of society 5.0. and what are the inhibiting and supporting factors. This study uses a qualitative approach with descriptive data analysis, researchers provide analysis and descriptions of various sources of information. The main data collection techniques are in-depth interviews, non-participant observation, and documentation studies. The results of this research are the various challenges faced by teachers in the era of society 5.0, making strengthening the professional competence of PAI teachers an absolute must, as is the program for strengthening the professional competence of PAI teachers was conducted at SMP Negeri 16 Samarinda. The program for strengthening the professional competence of PAI teachers includes: making learning contracts at the beginning of meetings with students, thinking out of the box in overcoming student problems, making HOTS questions, and making Classroom Action Research (PTK) every semester. The obstacle is the limited facilities and infrastructure in schools such as IT-based laboratories and scientific publications for the work of teachers. The spirit of learning from the teacher is a supporting factor that can help the success of the strategy for strengthening the competence of PAI teachers at SMP Negeri 16 Samarinda. (Era Society 5.0 membawa perubahan luar biasa dalam seluruh kehidupan manusia diberbagai bidang baik kesehatan, ekonomi, teknologi dan juga pendidikan. Dalam bidang pendidikan keberadaan guru menjadi sangat penting dalam rangka membentuk karakter building peserta didik untuk mengendalikan pengaruh negatif teknologi dan memanfaatkan teknologi dengan baik. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana tantangan guru PAI di era society 5.0’, bagaimana strategi penguatan kompetensi profesioal guru PAI di SMP Negeri 16 Samarinda yang sesuai dengan tuntutan di era society 5.0. dan apa saja yang menjadi faktor penghambat dan pendukungnya. Penelitian ini menggunakan pendekatan kualitatif dengan analisis data deskriptif, peneliti memberikan analisis dan deskripsi dari berbagai sumber informasi. Teknik pengumpulan data yang utama adalah wawancara mendalam, observasi non participant, dan studi dokumentasi Adapun hasil penelitian ini adalah adanya berbagai tantangan yang dihadapi oleh Guru di era society 5.0 menjadikan penguatan kompetensi profesional guru PAI mutlak harus dilakukan, sebagaimana program penguatan kompetensi profesional guru PAI yang dilakukan di SMP Negeri 16 Samarinda. Program penguatan kompetensi profesional guru PAI meliputi: pembuatan kontrak belajar pada saat awal pertemuan dengan siswa, berfikir out off the box dalam mengatasi persoalan siswa, membuat soal HOTS, dan membuat Penelitian Tindakan Kelas (PTK) setiap semester. Adapun hambatannya adalah keterbatasan sarana dan prasarana yang ada di sekolah seperti laboratorium berbasis IT dan publikasi ilmiah untuk hasil karya guru. Semangat belajar dari guru merupakan faktor pendukung yang dapat membantu suksesnya strategi penguatan kompetensi guru PAI di SMP Negeri 16 Samarinda.)